1994
DOI: 10.1007/bf00686263
|View full text |Cite
|
Sign up to set email alerts
|

Nation-wide randomized comparative study of doxorubicin, vincristine and prednisolone combination therapy with and without L-asparaginase for adult acute lymphoblastic leukemia

Abstract: A randomized clinical trial of combination chemotherapy for adult acute lymphoblastic leukemia (ALL) with doxorubicin, vincristine and prednisolone with and without L-asparaginase (AdVP vs L-AdVP) was conducted, involving 58 institutions throughout Japan. After reaching complete remission (CR), patients were treated with the same regimen for more than 2 years. Among 166 evaluable cases of the 198 cases enrolled, CR rates were 63.1% (53/84) with AdVP and 64.6% (53/82) with L-AdVP (P = 0.837). Median survival ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A wide range of rates of toxicities associated with PEG-ASP have been published. 5,6,1720 A historical cohort of patients from University of Southern California, Cleveland Clinic, and MD Anderson Cancer Center receiving PEG-ASP (median age: 33 years, range: 17–68) demonstrates that the rates of toxicity reported in the literature were much lower than we observed. These authors report 36% hepatotoxicity, 5% pancreatitis, and 8% thrombosis (all grades 3–4) in a cohort of 76 adult patients.…”
Section: Discussionmentioning
confidence: 47%
“…A wide range of rates of toxicities associated with PEG-ASP have been published. 5,6,1720 A historical cohort of patients from University of Southern California, Cleveland Clinic, and MD Anderson Cancer Center receiving PEG-ASP (median age: 33 years, range: 17–68) demonstrates that the rates of toxicity reported in the literature were much lower than we observed. These authors report 36% hepatotoxicity, 5% pancreatitis, and 8% thrombosis (all grades 3–4) in a cohort of 76 adult patients.…”
Section: Discussionmentioning
confidence: 47%
“…The role of L-asparaginase, while standard in pediatric protocols, is a challenge in adults at times due to the increased rate of adverse events. 41 In fact, in the UKALL 14 Trial, Patel et al 42, 43 demonstrated that asparaginase toxicity was the leading cause of induction-related mortality and the protocol was amended to omit asparaginase for patients over the age of 40. The MRC UKALL XII/ECOG 2993 23 regimen utilizes a similar structure to CALGB 8811.…”
Section: Established Treatmentsmentioning
confidence: 99%
“…Only one randomized trial (47) has analyzed the role of l‐asparaginase in induction therapy. No effect on CR rate was found, but L ‐asparaginase may have contributed to a longer remission duration.…”
Section: Treatment Of Adult Allmentioning
confidence: 99%